Second nature [compact disc, unabridged] : a gardener's education - Pollan, Michael (Brilliance Audio, 2009)
Second Nature captures the rhythms of our everyday engagement with the outdoors in all its glory and exasperation. With chapters ranging from a reconsideration of the Great American Lawn and a dispatch from one man's war with a woodchuck to an essay about the sexual politics of roses, Pollan has created a passionate and eloquent argument for reconsidering our relationship with nature.